Eczema apps conformance with clinical guidelines : a systematic assessment of functions, tools and content - van Galen, Louise Sandra (2021)
Background: Eczema is a prevalent complex skin condition requiring active disease monitoring and personalized education. No studies have assessed the quality of apps that aim to support eczema self-management.Objectives: To evaluate the quality and comprehensiveness of English, Chinese and Spanish self-management eczema smartphone apps for patients and/or their caregivers. Methods: A systematic assessment of eczema apps from July 2018 to November 2018. The assessment criteria were based on conformance with international eczema guidelines. The following domains were assessed: consistency and comprehensiveness of eczema-specific educational information; quality and comprehensiveness of eczema-specific tracking functions; compliance with health information best practice principles. Results: In total, 98 apps were assessed: 82 (84%) provided educational information; 38 (39%) tracking functions; and 13 (13%) both. We found that 34% (28/82) of apps provided misleading information, particularly regarding aspects of treatment and disease progression of eczema. Only 15% (12/82) provided international guideline supported information on pharmacological therapies and 16% (13/82) on nonpharmacological therapies. Among 38 apps with a tracking function, 82% (31/38) measured specific symptoms, disease severity or current skin condition and 89% (34/38) helped users to record medication usage including application of topicals. Environmental or dietary allergens were recorded by 34% (13/38). None of the included apps complied with all criteria for educational information, tracking functions or health information principles. Conclusions: Eczema apps have not yet reached their potential. The large variance in quality of eczema apps highlights the need for quality assurance mechanisms for health apps and guidance for clinicians that would enable them to make personalized recommendations for patients and caregivers.